2021
DOI: 10.1002/bse.2718
|View full text |Cite
|
Sign up to set email alerts
|

Which factors distinguish the different consumer segments of green fast‐moving consumer goods in Germany?

Abstract: Consumer segmentation is an important tool for dealing with the often strongly differing consumer preferences in many markets for fast-moving consumer goods.Therefore, this study analyses the factors that can distinguish the different consumer segments for green all-purpose adhesives in Germany. On the basis of an online survey with 709 respondents, we performed a choice experiment and segmented consumers based on their preferences for this product. We identified six consumer segments of which in particular Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 84 publications
5
36
0
1
Order By: Relevance
“…This was also reported for similar items by Kurka (2012) and Scherer et al (2017). Niedermeier et al (2021) showed that GCV act as a driver for purchase of bio-based products. Furthermore, GCV can be used to significantly separate green consumer segments from others in relation to bio-based products (Niedermeier et al, 2021).…”
Section: Green Consumer Values (Gcv)supporting
confidence: 75%
See 4 more Smart Citations
“…This was also reported for similar items by Kurka (2012) and Scherer et al (2017). Niedermeier et al (2021) showed that GCV act as a driver for purchase of bio-based products. Furthermore, GCV can be used to significantly separate green consumer segments from others in relation to bio-based products (Niedermeier et al, 2021).…”
Section: Green Consumer Values (Gcv)supporting
confidence: 75%
“…A general interest in bio-based products was also found in previous studies by Yue et al (2010), Kurka (2012), Behe et al (2013), and Kainz (2016). As in studies by Diamantopoulos et al (2003), Tanner and Wölfing Kast (2003), Hess et al (2013), Klein et al (2019), and Niedermeier et al (2021), this study has shown as well that socio-demographic characteristics have no relevance in the separation of the defined consumer groups.…”
Section: Discussion and Conclusion Main Findings Of The Studysupporting
confidence: 63%
See 3 more Smart Citations